2012
DOI: 10.4236/asm.2012.23007
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Women’S Emotional Experience of the First Trimester in a New Pregnancy after One or More Miscarriages: A Qualitative Interview Study

Abstract: Objectives: The aim of this study was to evaluate how Swedish women describe their emotional state of being during the eighth week through the eleventh week after they have become pregnant again after suffering a previous miscarriage. Method: A qualitative content analysis with an inductive approach has been used to analyze fourteen interviews that served as the data base for this study. The content analysis resulted in the development of five categories which evolved into one primary theme. Findings: The five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, after the actual evaluation of recurrent pregnancy loss remain unexplained in 60% of cases [ 2 ]. Qualitative studies indicated that a history of miscarriage could harm women and be associated with feeling anxious, development of psychological disorders, and affecting quality of life in this population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, after the actual evaluation of recurrent pregnancy loss remain unexplained in 60% of cases [ 2 ]. Qualitative studies indicated that a history of miscarriage could harm women and be associated with feeling anxious, development of psychological disorders, and affecting quality of life in this population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they may regard their pregnancy loss as a personal failure accompanied by feelings of their own guilt ( Wong et al, 2003 ; Adolfsson et al, 2004 ). It could also be argued that women who have had to deal with a pregnancy loss in their past are emotionally distancing themselves from their unborn child due to fears of another pregnancy loss ( Adolfsson et al, 2012 ). However, studies on the impairment of prenatal attachment in subsequent pregnancies after a pregnancy loss provided mixed results ( Tsartsara and Johnson, 2006 ; Alhusen, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be a very emotionally distressing event in a woman's life who has had high expectations of giving birth to a baby and then losing those hopes and dreams. The miscarriage can also be physically demanding with the resulting pain and bleeding [4,11,12].…”
Section: Environmental Factorsmentioning
confidence: 99%